Anti-inflammatory effect of Statins in reducing the exacerbation and mortality rates of COPD patients: a review study - Shomi, Iffat Ara (BRAC University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.